Awareness, Knowledge and Perception of Female Genital Mutilation and Cutting (FGM/C) Radio Campaign and Practice among Women in Imo State - , Adeline Nkwam-Uwaoma; , Ifeoma C. Ojiakor; , Joy C. Onovo (Archives of Current Research International, 2019)
The media play a crucial role in society. They educate, entertain, and inform their audience. On this note, the mass media has been a platform to inform and educate women on diseases and negatives activities like female genital mutilation and cutting. Female genital mutilation and cutting (FGM/C) are carried out for various cultural, religious and social reasons within families and communities in the mistaken belief that it will benefit the girl child. However, there are no acceptable reasons that justify FGM/C. It is a harmful practice that has no health benefits but rather exposes the girl child to dangerous health hazards. It is against this backdrop that this study sought to assess the influence of radio in the campaign against female genital mutilation and cutting. Using the survey research design, the study sampled the perceptions of 394 respondents using the questionnaire as the instrument of data collection. Anchoring the study on The Health Belief Model, it was revealed that there are moderate awareness and knowledge level amongst women in Imo State about FGM/C. The study concluded that the awareness and knowledge level is responsible for the kind of perception found in the study. It was recommended that sensitization programmes like seminars should be organized for traditional rulers, religious leaders and other opinion leaders to enable them to use traditional media communication channels to further sensitize and mobilize the rural women so as to consolidate the gains of the campaign and ensure total eradication of the FGM/C practice and that every media outlet in the State should take up the responsibility of championing this course.